Effects of degree of substitution and irradiation doses on the properties of hydrogel prepared from carboxymethyl-sago starch and polyethylene glycol. (15th January 2021) - Zahib, Irma Raihana; Md Tahir, Paridah; Talib, Marina; Mohamad, Rosfarizan; Alias, Aisyah Humaira; Lee, Seng Hua
Graphical abstract: Highlights: Degree of substitution (DS) significantly affect the gel content and swelling of hydrogel. Irradiation dose exert significant effect on the properties of hydrogel with lower DS. Thermal stability of the hydrogel was improved by adding polyethylene glycol. PEG with higher molecular weight resulted in smoother hydrogel structure. Abstract: Carboxymethyl starch ( CMS) was produced from sago starch via carboxymethylation. The CMS with different degree of substitution (DS) ranges from 0.4 to 0.8 were mixed with polyethylene glycol (PEG) of different molecular weight and distilled water and the hydrogel was cured by electron beam irradiation with doses ranging from 25 to 35 kGy. The results revealed that CMS-PEG hydrogels with DS 0.4 give the optimum gel content when radiated at 30 kGy and with PEG 600. Thermogravimetric analysis (TGA) revealed that there are two phases exist in CMS with DS 0.4 in contrast to the three steps decomposition occurs in DS 0.6 and 0.8. It shows that the CMS with DS 0.4 is more thermally stable. Surface morphology revealed crosslinking among the blends when subjected into the radiation dose. The study shows both radiation and PEG addition improved most of the properties of CMS irrespective of the DS value.